Percutaneous Autologous Bone Marrow Injection for Delayed Union and Non-Union for Long Bone Fracture - Jha, Subash Chandra; Koirala, Shreel (Journal of College of Medical Sciences-Nepal, 2025)
Background Treating nonunion remains a significant challenge in orthopedic surgery. Approximately 5% to 10% of fractures result in delayed or nonunion, leading to impaired function and necessitating repeated hospitalizations and surgeries. The aim of this prospective study was to evaluate the effectiveness of percutaneous bone marrow injection for treating fractures with delayed union and nonunion following internal fixation. Methods Adult patient with closed long bone fracture treated surgically with internal fixation with acceptable alignment, good bone opposition and stable fixation who presented with delayed or non-union were included in the study. Desired amount of non-heparinized bone marrow was injected under image intensifier guidance immediately after aspiration. Second bone marrow injection was repeated at interval of 4-6 weeks of first injection. Serial X-rays were taken at each review until 9 month post procedure. Results The study included 27 patients with delayed union and 3 cases of nonunion of long bones, all of whom were treated with percutaneous autologous bone marrow injections. Our study demonstrated an 85.18% success rate in achieving union following bone marrow injection in case of delayed union while, 33.33% success in case of non-union. Our results were excellent in 53.33% (16/30) of cases, good in 23.33% (7/30), and poor in 23.33% (7/30). Conclusions The use of bone marrow to accelerate fracture healing is one of the promising methods of treating delayed union and non-union.